Integrasi Sosial Golongan Miskin di Perkotaan: Kajian Kasus di Jakarta - Achmad Fedyani Saifuddin (Antropologi Indonesia, 2005)
This study looks into the internal process of the urban poverty of Jakarta in terms of the flowering phenomena of building and maintaining specific social relations among the poor to fulfill their basic economic needs. These complex social relations and exchanges among the poor and non-poor-called social integration of the poor-make the boundaries between the two social categories blurred and flexible. The paradox of social and economic statuses of the people involved has made this integration possible. This phenomenon will make poverty reduction programs in Indonesia face more complicated problems. Key words: Urban poverty; specific social relations; poverty as process; poverty paradox; social integration.